Artificial Intelligence of Things in Smart Environments : Applications in Transportation and Logistics (De Gruyter Series on the Internet of Things ,, 2022)
This book focuses on the use of AI/ML-based techniques to solve issues related to IoT-based environments, as well as their applications. It addresses, among others, signal detection, channel modeling, resource optimization, routing protocol design, transport layer optimization, user/application behavior prediction, software-defi ned networking, congestion control, communication network optimization, security, and anomaly detection.